Konstruksi dan Ekspresi Identitas Gender Kontemporer di TikTok - M Supriyadi; Muhammad Iqbal; Diana Dewi Sartika; Ghina Reftantia; Erlisa Saraswati (Jurnal Studi Gender dan Anak, 2025)
This study examines how TikTok, as a social media platform, influences the construction and expression of users’ gender identities. Employing a descriptive qualitative approach and discourse analysis, this research explores how symbols, language, and narratives within TikTok content reflect and challenge traditional gender roles. TikTok has emerged as an expressive and inclusive space for nonbinary and LGBTQ+ individuals to explore identity, foster interaction, and build social solidarity. The platform's algorithmic features allow for the rapid dissemination of alternative gender narratives and the formation of digital communities. While TikTok presents significant opportunities for empowerment, the study also reveals challenges such as queerbaiting, algorithmic bias, and normative body and gender expectations that may negatively impact users’ mental health. TikTok is thus not merely an entertainment platform but also a site of social contestation in redefining gender expression in the digital age. The findings conclude that TikTok plays a critical role in contemporary gender identity construction, despite ongoing structural and cultural obstacles.